2015
DOI: 10.5194/amt-8-5237-2015
|View full text |Cite
|
Sign up to set email alerts
|

Adaption of the MODIS aerosol retrieval algorithm using airborne spectral surface reflectance measurements over urban areas: a case study

Abstract: Abstract. MODIS (MOderate-resolution Imaging Spectroradiometer) retrievals of aerosol optical depth (AOD) are biased over urban areas, primarily because the reflectance characteristics of urban surfaces are different than that assumed by the retrieval algorithm. Specifically, the operational "darktarget" retrieval is tuned towards vegetated (dark) surfaces and assumes a spectral relationship to estimate the surface reflectance in blue and red wavelengths. From airborne measurements of surface reflectance over … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…MDT does not provide aerosol retrieval over very bright surface (i.e., desert) and over snow and ice regions. In addition, several validation studies have shown that MDT AOD retrievals over urban area are positively biased with respect to AERONET AODs Jethva et al, 2007;Hyer et al, 2011;Gupta et al, 2013;Munchak et al, 2013). These studies have shown that the major source of bias in the MDT over cities is that the city surface does not behave as a vegetated "dark" target.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MDT does not provide aerosol retrieval over very bright surface (i.e., desert) and over snow and ice regions. In addition, several validation studies have shown that MDT AOD retrievals over urban area are positively biased with respect to AERONET AODs Jethva et al, 2007;Hyer et al, 2011;Gupta et al, 2013;Munchak et al, 2013). These studies have shown that the major source of bias in the MDT over cities is that the city surface does not behave as a vegetated "dark" target.…”
Section: Introductionmentioning
confidence: 99%
“…Several other research attempts have been made to change the surface scheme in the MDT for particular urban regions and produce better AOD retrievals for those specific cities (de Almeida Castanho et al,2007Li et al, 2005;Wong et al, 2011;Zha et al, 2011;Li et al, 2012;Escribano et al, 2014;Jäkel et al, 2015). Instead of a retrieval focused on only one city, we seek a surface parameterization that is valid for cities across the globe.…”
Section: Introductionmentioning
confidence: 99%
“…Due to an increase of noise at the edges of the measured spectra, the final data are provided for 400 and 1800 nm wavelength, only. The measurement uncertainties are related to the radiometric and spectral calibration and to the correction of the cosine response which sum up to a total wavelength-dependent uncertainty ranging between 3 and 14% 52 .…”
Section: Cgr-4mentioning
confidence: 99%
“…MDT does not provide aerosol retrieval over very bright surface (i.e., desert) and over snow and ice regions. In addition, several validation studies have shown that MDT AOD retrievals over urban area are positively biased with respect to AERONET AODs (Levy et al, 2010;Jethva et al, 2007;Hyer et al, 2011;Gupta et al, 2013;Munchak et al, 2013). These studies have shown that the major source of bias in the MDT over cities is that the city surface does not behave as a vegetated "dark" target.…”
Section: Introductionmentioning
confidence: 99%
“…Several other research attempts have been made to change the surface scheme in the MDT for particular urban regions and produce better AOD retrievals for those specific cities (de Almeida Castanho et al,2007Li et al, 2005;Wong et al, 2011;Zha et al, 2011;Li et al, 2012;Escribano et al, 2014;Jäkel et al, 2015). Instead of a retrieval focused on only one city, we seek a surface parameterization that is valid for cities across the globe.…”
Section: Introductionmentioning
confidence: 99%